Analisis Sitiran Karya Ilmiah Dosen IAIN Purwokerto Tahun 2015-2017 - A. Luthfi Hamidi; Indah Wijaya Antasari; Ulfah Rulli Hastuti (IAIN Ponorogo, 2019)
This study aims to make a citation analysis of the scientific paper of a IAIN Purwokerto lecturer that has been published in an internal journal within three years (2015-2017). Using a quantitative approach is bibliometrics, a branch of library science that deals with statistics (mathematics). The population is all literature cited in scientific paper by the IAIN Purwokerto lecturers. Sampling of all lecturers' scientific papers that have been published in the journals Ibda, Almanahij, JPA, el-Jizya, Communica and Insania (6 journals) at 2015-2017. The data was obtained from the bibliography (citation) of the scientific paper of lecturers who had cited a number of 3,460 literature. The results of this study indicate that the form of literature that is widely cited is in the form of books (73.06%), the half-life of the literature is 13.5 years, and the availability of collections in the library is 54.42%. In addition, there are still alternative titles / library collection that make it possible to become an alternative reference material, namely a number of 156 library collection. It is recommended to lecturers in the IAIN Purwokerto environment to take part in the reference manager training, namely the application of writing citations (such as zotero or mendeley) so that writing of citation is more basic. This study recommends that an advanced bibliometric study be carried out, to dig deeper into the scientific paper of the IAIN Purwokerto academic community.